2012
DOI: 10.1007/s00464-012-2356-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term surgical outcomes and operative risks of laparoscopic total gastrectomy (LTG) for gastric carcinoma: experience at a large-volume center

Abstract: LTG is a feasible and acceptable procedure for treatment of middle or upper early gastric cancer. Further refinement of anastomosis techniques and considerable experience of laparoscopic gastrectomy are required for proper application of LTG in gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 28 publications
5
41
0
3
Order By: Relevance
“…We have performed LATG with the purse-string suture anastomosis in 100 patients with clinical stage I gastric cancer. Compared with the previous Korean studies and a small-scale Japanese study evaluating the safety of LATG [5,6,12, 13], we were able to perform LATG with more favorable surgical results in terms of operation time. Regarding the incidence of postoperative complications, our study showed better or similar results compared to previous studies of LATG.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…We have performed LATG with the purse-string suture anastomosis in 100 patients with clinical stage I gastric cancer. Compared with the previous Korean studies and a small-scale Japanese study evaluating the safety of LATG [5,6,12, 13], we were able to perform LATG with more favorable surgical results in terms of operation time. Regarding the incidence of postoperative complications, our study showed better or similar results compared to previous studies of LATG.…”
Section: Discussionmentioning
confidence: 71%
“…The reconstruction required in LATG is technically much more difficult than that in LADG. Only a few Korean studies have evaluated the feasibility of LATG with more than 100 patients [5,6], so the safety of LATG is still controversial. We have performed LATG with the purse-string suture anastomosis on 100 patients with clinical stage I gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The surgical procedure for CLATG is more complex and challenging than that for laparoscopic distal gastrectomy, even for an experienced gastric surgeon. In particular, the reconstruction technique has not yet been well established in CLATG [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…However, laparoscopy-assisted total gastrectomy (LATG) has not been widely used for the treatment of gastric cancer because of its technical difficulty and complexity, including the reconstruction required and its oncological safety. The most important issue that needs to be resolved is the technique used for the reconstruction of an esophagojejunostomy during LATG [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of 118 laparoscopic total gastrectomies, male gender was independently associated with postoperative morbidity [15] . Overweight patients [i.e., body mass index (BMI) > 25 kg/m 2 ] are at an increased risk of complications; this was shown in a large prospective series of 1853 patients [16] .…”
Section: Surgical Risk Assessmentmentioning
confidence: 99%